1998
DOI: 10.1093/bja/81.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and potential therapeutic uses of cannabis

Abstract: Throughout history, cannabis has been used as a natural therapeutic herb. Indeed the discovery of the remains of a young girl in Jerusalem who died in childbirth sometime around the third century AD, revealed residues of cannabis in the pelvic region. 97 This strongly suggests that cannabis was used in medical practice in early human civilizations. Cannabis was first used as a medicine in Britain in the mid-nineteenth century by O'Shaugnessy, an army surgeon. While in India O'Shaugnessy witnessed at first hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 68 publications
1
34
0
2
Order By: Relevance
“…The principal psychoactive ingredient of CB is delta-9-tetrahydrocannabinol (THC), which mainly acts as a ligand for two types of human cannabinoid receptors, the CB1 and CB2 receptors (Ameri, 1999;Glass et al, 1997;Hirst et al, 1998). CB1 receptors are widely distributed in the human brain with particularly high densities in the frontal cortex, medial temporal lobes, basal ganglia (particularly the substantia nigra), and cerebellum (Cb), and lower densities in the sensory cortices, thalamus, and hypothalamus (Glass et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The principal psychoactive ingredient of CB is delta-9-tetrahydrocannabinol (THC), which mainly acts as a ligand for two types of human cannabinoid receptors, the CB1 and CB2 receptors (Ameri, 1999;Glass et al, 1997;Hirst et al, 1998). CB1 receptors are widely distributed in the human brain with particularly high densities in the frontal cortex, medial temporal lobes, basal ganglia (particularly the substantia nigra), and cerebellum (Cb), and lower densities in the sensory cortices, thalamus, and hypothalamus (Glass et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In open-label, uncontrolled studies, both smoked cannabis and oral cannabinoids have been reported to be effective analgesics (101). The onset of action is more rapid with smoking, but there are few situations in which this is an important consideration.…”
Section: Analgesiamentioning
confidence: 99%
“…When administered to humans, THC produces a wide range of effects, including increase in pulse rate, decreased blood pressure, muscle weakening, increased appetite, euphoria followed by drowsiness, depersonalization, altered time sense and decreased memory reflection, hearing becoming less discriminative and visual signals becoming sharper but distorted (Hirst et al, 1998). The effects of THC at the biochemical level were virtually unknown until recently.…”
Section: Cannabis Sativamentioning
confidence: 99%
“…The effects of THC at the biochemical level were virtually unknown until recently. Earlier pharmacological studies have suggested that THC and other active cannabinoids might act at specific receptor sites (see Hirst et al, 1998). The CB 1 and the CB 2 receptors for cannabinoids were discovered by Matsuda et al (1990) and Munro et al (1993) respectively, and were confirmed as being G-protein-coupled receptors that inhibit adenylate cyclase activity.…”
Section: Cannabis Sativamentioning
confidence: 99%
See 1 more Smart Citation